Kunst & Zwalm 1997. - Neutjens, Clem; Uytterhoeven, Jos (Zwalm : Boem vzw, 1997)
Amaya, Irma ; Becerra, Carlos ; Broodthaers, Marcel ; Byars, James Lee ; d'O, Honoré ; Debruyne, Luk ; Drieghe, Noel ; Van gaver, William ; Heugebaert, Catherine ; Lievens, Johan ; Mason, Timothy ; Merckaert, Patrick ; Michels, Alex ; Ryslavy, Kurt ; Sack, Stephen ; Stroobants, Jean-Marie ; Tahon, Johan
Biog. [2 p.]
Kunst & Zwalm 1997, Zwalm - Zwalmstreek, 06.09 - 14.9.1997
Nederlands & Frans
kunstcatalogus
Keywords: Zwalmstreek